The Role Of Eye Health Education In Improving Awareness Of Children's Vision Impairment Prevention - Sri Wahyu Budoyo Kusumo; Arraywed Yudita Wibowo; Ardhitya Furqon Wicaksono (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Visual impairment among elementary school children is a public health concern that significantly affects academic performance, cognitive development, and overall quality of life. Limited awareness and knowledge of eye health, along with inadequate early detection, contribute to the high prevalence of untreated visual problems in children. This study aimed to analyze the role of eye health education in increasing awareness of visual impairment prevention among elementary school students. A descriptive qualitative design with a case study approach was employed in a school-based eye health education program. Data were collected through direct observation, in-depth interviews with students and teachers, documentation review, and analysis of vision screening reports. Thematic analysis was conducted by linking field findings with health promotion theories. The results indicate that structured, contextual, and participatory eye health education effectively improves students’ knowledge of eye health, fosters positive attitudes, increases awareness of vision screening, and encourages preventive behaviors such as consistent use of corrective eyewear and controlled screen time. This study concludes that eye health education plays a strategic role as a promotive and preventive intervention in reducing the risk of visual impairment among children and should be sustainably integrated into school health programs.